Exchange Rate and Gold Price’s Effect on Jakarta Composite Index during Ukraine-Russian War - Gunadi, Patrisinus Ceasar; Robiyanto, Robiyanto (Magister Akuntansi - Universitas Atma Jaya Makassar, 2024)
This research aims to examine how exchange rates and gold prices influence the Indonesia Composite Index during the Ukrainian and Russian wars. The research object used in this research is the USD/IDR exchange rate, gold prices and Jakarta Composite Index (JCI) from February 24, 2022 to October 25, 2023. The data analysis technique uses Generalized Autoregressive Conditional Heteroscedasticity (GARCH). The results of this research indicate that the research model follows GARCH patterns. Furthermore, Rupiah exchange rate against the Dollar does not significantly influence the Indonesia Composite Index. Meanwhile, the price of gold influences significantly and has a positive influence on the Indonesia Composite Index. In conclusion, investors can pay attention to the price of gold because the price of gold has a significant influence in a positive direction on the Indonesia Composite Index.